Struktur Komunitas Mikroalga Air Tawar di Sungai Jangkok, Lombok Indonesia - Nining Purwati; Ervina Titi Jayanti; Miftahul Jannah (Postgraduate, University of Mataram, 2022)
The microalgae community structure in an aquatic ecosystem is strongly influenced by environmental factors. One of the rivers in Indonesia, located inhe island of Lombok, West Nusa Tenggara, is the Jangkok River. The Jangkok River is widely used by residents for activities, including industry, cultivation, waste disposal, and others. This study aimed to determine the structure of microalgae community in Jangkok River. This research was carried out with an exploration descriptive method by quantitative and qualitative approaches. Data were analyzed quantitatively by calculating the Shannon-Wiener diversity index (H’), Uniformity index (E) and Dominance index (d). The results showed that the diversity of microalgae was categorized as moderate (H' = 2.66), uniformity index (E = 0.66), and the dominance index indicate that there were no dominant species with a value (D = 0.13).